The Effect of Liquid Organic Fertilizer From Coconut Husk And Dolomite On Shallot (Allium Cepa L.) Growth And Yield - Jayanti, Kamelia Dwi; Tanari, Yulinda (Yayasan Pertanian Tropika Indonesia (YPTI), 2021)
Shallot is the most produced vegetable in Indonesia. The consumption of shallot per kg/capita/year is continuously increasing, therefore there is a need to ensure enough supply. The lack of nutrients in the soil is a problem in shallot production. Shallot needs macronutrients such as Nitrogen (N), Phosphorus (P), Potassium (K), and Calcium (Ca) to improve its yield and quality. The application of liquid organic fertilizer from coconut husk and dolomite can be the solution. This study was conducted using Factorial Randomized Block Design consisting of two factors, concentration of liquid organic fertilizer (0%, 10%, 20%, and 30%) and dolomite (with dolomite or without). The results showed that the application of 20% liquid organic fertilizer, the application of dolomite, and the combination of both (P2D1) had the highest value on fresh shallot bulbs weight per clumps and bulb weight after storage parameters, and had the lowest value on weight loss percentage parameter.